The planning and control of UK public expenditure, 1993-2015 - Rowena Crawford; Paul Johnson; Ben Zaranko (Institute for Fiscal Studies (IFS), 2018)
The last 25 years have seen two periods of public expenditure restraint in the UK (the 1990s and the 2010s) and one period of increased spending (between 2000 and 2010). Over that whole time, the Treasury has been responsible for controlling government spending, setting fiscal rules and the overall control framework, and ensuring that other departments stay within their spending limits. In this report, we use data on spending plans and out-turns to see what they can tell us about the efficacy of spending control under different regimes. As well as different fiscal environments, and consequently different overall fiscal rules, over the periods there have also been different measures and targets for spending. During the 1990s, the then Conservative government was aiming to reduce public spending as a fraction of national income, and was targeting for control a measure of public spending dubbed the 'new control total'. This covered around 85% of public spending, including local authority spending and 'non-cyclical' social security spending, on pensions for example. It excluded the more cyclical elements of social security and debt interest payments. [...]
Keywords: 330